THE UPBRINGING OF THE YOUNGER GENERATION IS THE FOUNDATION OF THE FUTURE - Qulmurodova.S.S (Western European Studies, 2025)
High world's vicinity of the young Avlan in this article tells us that educating the thinking of thinking, environmental awareness, and vigilance
Keywords: upbringing; education; behavior